2018
DOI: 10.1159/000495084
|View full text |Cite
|
Sign up to set email alerts
|

Long-Noncoding RNA Colorectal Neoplasia Differentially Expressed Gene as a Potential Target to Upregulate the Expression of IRX5 by miR-136-5P to Promote Oncogenic Properties in Hepatocellular Carcinoma

Abstract: Background/Aims: The long-noncoding RNA colorectal neoplasia differentially expressed (CRNDE) gene was first found to be activated in colorectal neoplasia. Now, it also has been found to be upregulated in many other solid tumors. Whether CRNDE affects tumorigenesis remains unknown. Methods: We conducted bioinformatics, real-time polymerase chain reaction (PCR), Western blot analysis, cell proliferation assay, colony formation assay, wound healing assay, cell migration and invasion assays, RNA immunoprecipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In particular, it has recently been reported that CRNDE controls proliferation and survival of the U266 MM cell line by acting as a molecular sponge for miR-451 [29]. Further, another microRNA, miR-136-5p, which is observed to be sponged by CRNDE in several tumours [49,[54][55][56] has been reported to target the IL6R transcript in rat microglial cells [57]. However, miR-451 and miR-136-5p were not detectable by real time RT-PCR in either wild type or CRNDE Δ/Δ KMS11 cells, or in the NC1 CRISPRi cell lines used in the current study (data not shown), indicating that the effects of CRNDE in these models was not mediated via these miR-NAs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has recently been reported that CRNDE controls proliferation and survival of the U266 MM cell line by acting as a molecular sponge for miR-451 [29]. Further, another microRNA, miR-136-5p, which is observed to be sponged by CRNDE in several tumours [49,[54][55][56] has been reported to target the IL6R transcript in rat microglial cells [57]. However, miR-451 and miR-136-5p were not detectable by real time RT-PCR in either wild type or CRNDE Δ/Δ KMS11 cells, or in the NC1 CRISPRi cell lines used in the current study (data not shown), indicating that the effects of CRNDE in these models was not mediated via these miR-NAs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-136-5p was identified as a potential target for FAM83H-AS1; this was further confirmed by qRT-PCR, luciferase activity, and the RIP assays. MiR-136-5p was found to inhibit cell proliferation, migration and invasion in renal cell carcinoma [34], liver cancer -by regulating IRX5 [35], and in colon cancer, through targeting LRH-1/Wnt signaling [36]. MiR-136 also inhibits cell survival, proliferation, cancer stem cell spheroid formation, and tumor angiogenesis in paclitaxel-resistant ovarian cancer cells by targeting Notch3 [37].…”
Section: Discussionmentioning
confidence: 99%
“…The altered expression of CRNDE is observed in many types of cancers, including hepatocellular carcinoma and acute myeloid leukemia (AML). [76][77][78] Le Dieu et al reported that there was a dramatic increase in CRNDE in both CD4(+) and CD8(+) cells in AML patients, which indicates that loss of CRND expression may be associated with the transition to a single-positive stage. 78 Keller et al also found that CRNDE involves cellular differentiation.…”
Section: Crndementioning
confidence: 99%